Hybrid PCM-steam thermal energy storage for industrial processes – Link between thermal phenomena and techno-economic performance through dynamic modelling - Niknam, Pouriya H; Sciacovelli, Adriano (Applied energy, 2023)
•A dynamic model for HyTES is implemented to estimate the performance and optimise the design.•The surpassing efficiency of HyTES arises from PCM latent heat and the superior performance of the steam accumulator in the hybrid system.•HyTES stores up to 45% more energy than a conventional steam accumulator.•The incorporation of HyTES leads to 5% reductions in CAPEX and stream generation cost.•The dominant design parameter for HyTES are the PCM latent heat and the charging time. This study aims to assess the performance and economics of novel hybrid thermal energy storage (HyTES) for industrial applications, linking performance to thermal phenomena occurring within the system. The storage hybridisation concept is based on coupling latent heat storage modules containing high-temperature Phase Change Materials (PCMs) with a fast-response steam accumulator. Such hybrid storage, where heat is stored in both forms of steam and latent heat of PCMs, has the potential to capture excess heat produced by the steam generator of any industrial processes, which can then be used at peak times. HyTES performance is dynamically modelled during charging, idle, and discharging stages. The results show that the HyTES provides 14% extra energy storage capacity than the existing steam accumulator within an identical total volume. Furthermore, the study provides technical analysis of HyTES, and thorough comparison between configurations with different PCM volumes, PCM types and charging times. This is essential to ultimately quantify the whole range of benefit of hybrid energy storage. The sensitivity analysis reveals that Incorporating the HyTES significantly improves energy capacity, and the degree of improvement is mainly affected by the charge duration, approximately 15% after 1 h, and 45% after 4 h of charging. Furthermore, it is shown how the PCM properties affect the performance of HyTES. Finally, the CAPEX and O&M cost of the entire system are assessed in different scenarios and found to be 5% less when HyTES replaces the conventional SA.